Poetics of history : Rousseau and the theater of originary mimesis - Lacoue-Labarthe, Philippe (Fordham University Press, 2019)
Poetics of History places Rousseau at the origin of modern speculative philosophy by showing that his thinking on the theater, despite its dependence on a false and conventional reading of Aristotle, nonetheless articulates a radical thinking of originary mimesis, and, well before Hegel, an understanding of catharsis as Aufhebung.